Oral health status of young adults in Serbia: Clinical and non-clinical assessment of undergraduate students in Belgrade - Lisul Bogdan; Grga Đurica (Serbian Medical Society - Dental Section, Belgrade, 2021)
Introduction Since 1987, there has been little information on oral health (OH) status of young adults aged 19 to 26 in Serbia. This study aimed to investigate the trends in OH status and OH-related quality of life (OHRQoL) of undergraduate student population in Belgrade in 2012. Materials and methods The study included a total of 699 students of different study fields who underwent a dental examination, with 530 of them agreeing to an assisted survey and 275 forgoing a periodontal assessment. The survey consisted of six sections - basic information, socio-demographic data, oral healthcare use and habits, risk factors, OH self-assessment and OHRQoL. Clinical assessment was performed using the Decayed, Missing, Filled teeth (DMFT) index; Gingival Index; Clinical Attachment Level; Community Periodontal Index, and Plaque index. OHRQoL was evaluated through a modified OH Impact Profile (OHIP-14). Results The mean DMFT of the examined population was 10.24 (standard deviation [SD] 5.33). Students from East and South Serbia (DMFT=8.69 [SD=4.93]), technical study field (DMFT=8.84 [SD=4.94]), with mother's having a university degree (DMFT=9.33 [SD=5.15]) and with satisfactory OH (DMFT=8.94 [SD=4.76]) were all significantly associated with lower DMFT. A significantly lower OHRQoL score was observed in students with satisfactory self-reported OH (Score=9.48 [SD=1.44]). The periodontal assessment showed no significant differences across all values of observed indexes. Conclusion The mean DMFT of Belgrade's young adults' population has decreased from 1987 to 2012 from 12.5 to 10.4. Self-reported OH is significantly associated with both the DMFT values and OHRQoL.